Release of contaminant elements from bentonites to wine: a contribution to achieve a test solution - Catarino,Sofia (2006)
The release of mineral elements from six bentonites to wine and to the test solution established by the OIV was evaluated in order to compare the extraction performance of both solutions. Significant differences between wine and tartaric solution results for thirty-four mineral elements analysed by AAS, ETAAS and ICP-MS were observed, suggesting that the extraction solution proposed by the OIV is not suitable for bentonite quality control purposes. Taking into account bentonite maximum extractable amounts defined by the OIV, some samples showed higher concentrations for Na (B3 and B8), Al (B8), Fe (B5) and As (B9). An additional extraction essay involving two bentonites, wine and two complex test solutions containing the major mineral elements of wine (K, Ca, Na and Mg) and protein (wine protein and BSA) was carried out. Significant differences were observed for all elements with exception of Sc, Mn, Co, W and Bi. For several elements, such as Na, Mg (test solution with BSA) V, Ni, Ga, Zr, Cd, In, Sb, Tl and U, the similarity of wine and test solutions content variations was satisfactory. The protein nature of test solutions seemed to have a decisive role in some element changes, probably related to wine protein and BSA distinct volume. In general, the test solution containing wine protein was a slightly better simulator of wine performance. However, the above mentioned test solutions did not simulated wine performance in a total satisfactory way, and further work should be performed on extraction solution composition.